Insertion and management of short peripheral catheters in adults by registered nurses. - Coomarasamy, Jeya Devi; Mohd Mokhtar, Hanida Hani; Hassan, Hamidah; Ong, Swee Leong; Marimuthu, Jayanthi; Rozali, Zainudin; Saleh, Siti Nor Fazira; Ismail, Lina; Mohd Anuar, Norziana; Hamrah, Muhammad Hamzihadi (Infusion Nurse Society, 2023)
The Guideline for the Insertion and Management of Short Peripheral Catheters (SPC) in Adults for Registered Nurses was developed based on best practices with the aim of preserving vessel health and improving patient outcomes.